Selection and implementation of a consortial e-resource management system: The University of Missouri System's experience - Thompson, Jennifer France (Journal of electronic resources librarianship, 2021)
Implementing effective Electronic Resource Management Systems (ERMS) is a continuing challenge for library consortia. The E-Resources Cooperative Office of the University of Missouri System identified a need to implement an ERMS to manage its consortially-licensed electronic resources more effectively, transparently and cooperatively. The author details the experience of selecting and implementing an ERMS to better meet the current e-resource management needs of member libraries and the consortium office. Leveraging the capabilities of an ERMS will also allow the consortium to more proactively engage in special projects and additional e-resources endeavors to benefit its members.